2021
DOI: 10.3390/ijms222010973
|View full text |Cite
|
Sign up to set email alerts
|

Organ Specificity and Heterogeneity of Cancer-Associated Fibroblasts in Colorectal Cancer

Abstract: Fibroblasts constitute a ubiquitous mesenchymal cell type and produce the extracellular matrix (ECM) of connective tissue, thereby providing the structural basis of various organs. Fibroblasts display differential transcriptional patterns unique to the organ of their origin and they can be activated by common stimuli such as transforming growth factor-β (TGF-β) and platelet-derived growth factor (PDGF) signaling. Cancer-associated fibroblasts (CAFs) reside in the cancer tissue and contribute to cancer progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…In recent years, tumor microenvironment (TME) seems to have an emerging role in tumorigenesis, tumor growth, metastasis and resistance to therapy [ 1 , 2 ]. TME consists of the extracellular matrix (ECM) and different cells and micromolecules (tumor cells, immune cells, vasculature and cancer-associated fibroblasts (CAFs)) [ 2 , 3 ]. All of them are involved in tumor growth, mainly by activating different pathways, and provide information on progression to one another [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, tumor microenvironment (TME) seems to have an emerging role in tumorigenesis, tumor growth, metastasis and resistance to therapy [ 1 , 2 ]. TME consists of the extracellular matrix (ECM) and different cells and micromolecules (tumor cells, immune cells, vasculature and cancer-associated fibroblasts (CAFs)) [ 2 , 3 ]. All of them are involved in tumor growth, mainly by activating different pathways, and provide information on progression to one another [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts are the main stroma components leading to ECM remodeling in the connective tissue [ 6 , 7 ]. They are mesenchymal cells that can be differentiated under specific signals in various organs [ 3 ]. CAFs are fibroblasts with a crucial role in tumor growth and metastasis by interacting with cancer cells via various mechanisms, such as exosomes, production of cytokines or cell-to-cell contact [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation of the modulator SMAD proteins, SMAD2 or SMAD3, leads to form heteromeric complexes with SMAD4, [18]. The SMAD complexes translocate to the nucleus and interact with transcription factors to control target genes [19]. Reprogramming of gene expression leads to the suppression of gene defining epithelial phenotypes and activation of genes defining mesenchymal phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…CRC cell-derived IL-1α augments angiogenesis by modulating stromal cells within the TME and facilitates metastases to distant organs, including peritoneal and liver metastases [109]. While the role of CAFs in CRC has been extensively reviewed [110,111], Heichler et al [112] showed that IL-6 and IL-11 are frequently upregulated in CRC, activate STAT3 in CAFs, and are associated with poor survival. Indeed, they reported that constitutive activation of STAT3 in colon fibroblasts promotes tumorigenesis in an experimental model of CRC.…”
Section: Cytokines and Chemokines Modulate Crc Microenvironmentmentioning
confidence: 99%